Role of summer legumes on productivity of maize (Zea mays)- wheat (Triticum aestivum)cropping system on sandy-loam soil of western Uttar Pradesh - SHARMA, G L; MAHAPATRA, B S; SINGH, A K; PANDEY, B M (The Indian Journal of Agricultural Sciences, 2013)
A 2-year field experiment was conducted during 1990-91 and 1991-92 on a sandy-loam soil of Modipuram, tostudy the effect of summer legumes on growth and yield of maize (Zea mays L.) in rainy (kharif) season on wheat(Triticum aestivum L. emend. Fiori & Paol) in the winter (rabi) in a maize-wheat system. Summer cropping of groundnut(Arachis hypogaea L.), cowpea [Vigna unguiculata (L.) Walp.] for fodder and greengram, (Phaseolus radiatus L.) hadsignificant effect on growth, yield and its attributes and nitrogen uptake on maize. Grain yield recorded for maize grownafter groundnut was at par with that after cowpea (fodder), but was significantly higher over greengram and fallow plots.Increasing each level of nitrogen brought significant improvement in the growth and yield attributes and finally grainyield even up to 120 kg N/ha, though yield obtained with 80 and 120 kg N/ha were at par. Two years mean data showedthat summer legumes. could contribute nitrogen equivalent to 40-80 kg N/ha Summer cropping of groundnut andcowpea (fodder) significantly increase the grain yield of wheat compared with the greengram and fallow, only duringthe second year of experimeptation. Grain yield of wheat also increased significantly with increase in level of nitrogenup to 120 kg N/ha during both the years, though yield obtained with 120 and 80 kg N/ha was at par during second year.